Shuang-Huang-Lian injection induces an immediate hypersensitivity reaction via C5a but not IgE - Yuan Gao (Nature Portfolio, 2018)
Abstract Among traditional Chinese medicine injections, intravenous Shuang-Huang-Lian (IV-SHL) has the highest incidence of injection-induced immediate hypersensitivity reactions (IHRs). The precise mechanisms of IV-SHL-induced IHRs remain ambiguous. In this study, we investigated the mechanisms of SHL injection (SHLI)-induced IHRs. Our data showed that serum total IgE and mouse mast cell protease 1 (MMCP1) levels were higher in the SHLI antiserum; however, these effects of SHLI disappeared in the antibiotic-treated mice. SHLI caused intraplantar vasopermeability and shock during the first local or systemic injection. SHLI-induced nonallergic IHRs were attributed to its intermediate fraction F2 (the extract of Lonicerae Japonicae Flos and Fructus forsythiae), and could be blocked by antagonists for histamine or C5a, rather than PAF or C3a. Eight constituents of F2 were able to directly activate C5 to promote local vasopermeability at the mg/mL level. In conclusion, SHLI-induced IHRs are not mediated by IgE. SHLI or its F2 can directly activate blood C5. Subsequently, C5a is likely to provoke histamine release from its effector cells (e.g., mast cells and basophils), indicating that histamine is a principal effector of IHRs induced by SHLI.